Etika Jurnalistik, Perempuan dan Pemberitaan Pelecehan Seksual di Media Online - Kadek Kiki Astria; Ahmad Khairul Nuzuli; Fitri Handayani (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2021)
This study discusses the reporting of Sexual Harassment in the online media Tribunnews.com from the standpoint of journalistic ethics and sexual harassment. Media reporting is demanded to be gender responsive, but media content cannot be separated from market interests. The method used in this research is ethnographic content analysis. The results show that some of the publications on Tribunnews.com have met Article 5 Journalistic Code of Ethics, but there are some that have not been gender responsive, which tends to display the workplace address, place of study and residence of victims of immoral crime.